MENGINTEGRASIKAN LAYANAN PENDIDIKAN NONFORMAL DAN PENDIDIKAN FORMAL UNTUK MENINGKATKAN KUALITAS PENDIDIKAN DI SEKOLAH - Rulam Ahmadi (Prodi Ilmu Administrasi Negara, 2015)
The quality of education in schools still showed no improvement of symptoms significantly. Figures failure in national examinations continued in various regions. Schools may have been trying to improve the quality of education, however, probably because the strategies are less effective, then the result is not effective. The school has a lot of limitations to truly improve the quality of education, which include limited time, rigid curriculum, and teachers' limited capabilities. Therefore, it is necessary the effective solution to resolve the issue. Integrating non-formal and formal education in schools is an alternative that should be considered. Non-formal education system with the characteristics and flexible implementation can offer services to contribute to improving the quality of education in schools. The studentscantaketheirfree timetofollow theguidance of learninginnon-formal educationinstitutions, namelythe so-calledtutoring.Servicesonnon-formal education, especiallycurriculum(materials) thatcan beadapted tothe learnersand thelearningtimecan beadjustedbyspare timelearnersis possibletocomplement theneeds ofeducation in schools, theneed forimproving the quality ofeducation at all levelsof formaleducation.